The The Archetypal Journey of the Kawi: A Jungian Psychological Reading of the Discourse of Kalepasan in Kakawin Panca Dharma - Ni Made Ari Dwijayanthi; I Nyoman Suarka; I Ketut Sudewa; I Gusti Ayu Agung Mas Triadnyani (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study reinterprets Kakawin Panca Dharma through Carl Gustav Jung’s analytical psychology, viewing kalepasan (liberation) as a symbolic manifestation of the poet’s (kawi’s) inner transformation through the process of individuation. While previous studies have treated Kakawin Panca Dharma as a theological or ethical text, this paper argues that the discourse of kalepasan reflects archetypal structures of the psyche—shadow, anima, and Self—within the creative process of the kawi-wiku. Through a qualitative hermeneutic method integrating philological reading and Jungian symbolic interpretation, this research uncovers how motifs of silence (sunya), detachment (putus), and purification (wimala) embody stages of psychological transformation. The findings reveal that Kakawin Panca Dharma serves as a “temple of language,” where poetic creation functions as an act of active imagination, integrating conscious and unconscious dimensions of the self. Liberation thus signifies not only spiritual transcendence but psychological wholeness—the realization of the Self archetype.